Avian sarcoma virus gag precursor polypeptide is not processed in mammalian cells. - Vogt, V M (1982)
We studied intracellular avian gag proteins (internal structural proteins of virions) in several mammalian cell lines transformed by Rous sarcoma virus. All lines examined contain gag antigens as determined by radioimmune assay. We used the techniques of protein blotting from polyacrylamide gels, which detects nanogram quantities of viral protein, to investigate the size of intracellular viral polypeptides. All of the lines that contained enough viral protein to be amenable to this type of analysis synthesized Pr76, the avian sarcoma virus gag precursor polypeptide, but failed to process it into mature virion proteins. In some cell lines, the recovery of Pr76 was greatly enhanced by the addition of a mixture of protease inhibitors, including the sulfhydryl-blocking reagent N-ethylmaleimide, to the lysis buffer. At least several of the mammalian cells also synthesized a viral polypeptide the size of Pr180, the precursor to reverse transcriptase. Since Rous sarcoma virus does not replicate or replicates extremely poorly in mammalian cells, the lack of processing suggests that cleavage and virion assembly are invariably associated.